Application Of Seismic Attributes Technique To Post-stack Seismic Data For Structural Model Delineation - Marjan, Syarydha Fassha (2019)
Normal post-stacked seismic sections sometimes hide important information. Efforts have over the years to enhance the readability of the seismic sections using seismic attributes. Various seismic attributes are currently active usage in the oil and gas industry. In the present study, post-stacked seismic attributes are used. Among the long list of such attributes, three attributes are chosen for this study are instantaneous frequency, instantaneous amplitude and instantaneous phase. The good performance for the instantaneous frequency attribute filter on post-stacked data rely on frequency bands chosen. It is noted that different rock formations have different frequencies. Hence, choosing different frequency bands can help increase the resolution on the post-stacked seismic sections. The main objectives of this study are to identify the narrow-band frequency for enhancing delineation the target formation and to analyze the reaction of sets of post-stack seismic data. To reach the objectives, the narrow-band frequency was extracted out from full-range frequency. Three types of post-stack seismic data; relative amplitude, automatic gain control and a crooked were applied selected instantaneous attributes. The result shows that reliable contrast of the high and low frequency at shallow and deeper part respectively by using relative amplitude type post-stack seismic. For automatic gain control post-stack seismic data, the frequency is in poor appearance and for a seismic crooked type post-stack seismic data, the high frequency vertical lines are obvious exposed.